The CPEB Protein Orb2 Has Multiple Functions during Spermatogenesis in Drosophila melanogaster. - Xu, S.; Hafer, N.; Agunwamba, B.; Schedl, P. (PLoS Genetics, 2012)
Cytoplasmic Polyadenylation Element Binding (CPEB) proteins are translational regulators that can either activate or repress translation depending on the target mRNA and the specific biological context. There are two CPEB subfamilies and most animals have one or more genes from each. Drosophila has a single CPEB gene, orb and orb2, from each subfamily. orb expression is only detected at high levels in the germline and has critical functions in oogenesis but not spermatogenesis. By contrast, orb2 is broadly expressed in the soma; and previous studies have revealed important functions in asymmetric cell division, viability, motor function, learning, and memory. Here we show that orb2 is also expressed in the adult male germline and that it has essential functions in programming the progression of spermatogenesis from meiosis through differentiation. Like the translational regulators boule (bol) and off-schedule (ofs), orb2 is required for meiosis and orb2 mutant spermatocytes undergo a prolonged arrest during the meiotic G2-M transition. However, orb2 differs from boule and off-schedule in that this arrest occurs at a later step in meiotic progression after the synthesis of the meiotic regulator twine. orb2 is also required for the orderly differentiation of the spermatids after meiosis is complete. The differentiation defects in orb2 mutants include abnormal elongation of the spermatid flagellar axonemes, a failure in individualization and improper post-meiotic gene expression. Amongst the orb2 differentiation targets are orb and two other mRNAs, which are transcribed post-meiotically and localized to the tip of the flagellar axonemes. Additionally, analysis of a partial loss of function orb2 mutant suggests that the orb2 differentiation phenotypes are independent of the earlier arrest in meiosis.